High-grade transformation of papillary cystadenocarcinoma with p16 immunoreactivity arising from the base of tongue - Katherine Larrabee; Jena C. Patel; Terrance J. Lynn; Iman Sarami; William Quinones (Elsevier, 2019)
Papillary cystadenocarcinoma (PCC) is a rare malignant salivary gland neoplasm that accounts for less than 0.2% of primary salivary gland tumors. These tumors are characterized by the presence of invasive cystic and ductal structures and well-defined papillary endophytic projections with or without mucin production. PCC are generally low-grade indolent tumors with relatively low rate of regional lymph node metastasis. Since malignant tumors are rare, we report a case of papillary cystadenocarcinoma at the base of tongue with focal high-grade transformation and p16 positive immunoreactivity in an 80-year-old male.